Annotated checklist and illustrated key to parasitoids (Hymenoptera: Diapriidae, Eulophidae and Pteromalidae) of fruit flies (Diptera, Tephritidae) in Brazil - Shimbori, Eduardo Mitio; Costa, Valmir Antonio; Zucchi, Roberto Antonio (Zootaxa, 2020)
The hymenopteran parasitoids of pest species of Tephritidae in Brazil are best known by their most prominent species, members of Braconidae and Figitidae. Species in the less-studied families Diapriidae, Eulophidae and Pteromalidae, which are mostly pupal parasitoids, have been largely neglected and the literature on these groups is sparse and scattered. Therefore, their importance as natural enemies of fruit flies is likely underestimated. Here, we present a parasitoid-host-plant checklist of all diapriids, eulophids and pteromalids that parasitize fruit flies of economic importance in Brazil, namely Anastrepha species and Ceratitis capitata. A compilation of information of the seven species of these parasitoids occurring in Brazil—Coptera haywardi Loiácono and Trichopria anastrephae Lima (Diapriidae), Tetrastichus giffardianus Silvestri (Eulophidae), Pachycrepoideus vindemmiae (Rondani), Spalangia endius Walker, S. gemina Bouček and S. simplex Perkins (Pteromalidae)—including their taxonomic status, general biology, and potential as biocontrol agents, is presented. Additionally, we provide an illustrated key to species, aiming to highlight key morphological features and facilitate identification at species level, stimulating future research on these groups.